Fertility-sparing management of low-grade endometrial stromal sarcoma: analysis of an institutional series and review of the literature. (December 2015) - Laurelli, Giuseppe; Falcone, Francesca; Scaffa, Cono; Messalli, Enrico M.; Del Giudice, Maurizio; Losito, Simona; Greggi, Stefano
Abstract: Objective: Low-grade endometrial stromal sarcoma (LG-ESS) is a rare malignancy, often occurring before menopause. There is no consensus regarding its optimal management. Total hysterectomy and bilateral salpingo-oophorectomy precludes future fertility and may thus be undesirable by women wishing to maintain their reproductive potential. However, experience of fertility-sparing management in LG-ESS is very limited. In this paper, the disease outcome is presented in six young women with LG-ESS conservatively treated by combined hysteroscopic resection and hormonal therapy. Study design: From October 2009 to February 2013, at the Gynecologic Oncology Department of the National Cancer Institute of Naples, six women, with early-stage LG-ESS aged 18–40 years who desired childbearing and/or retaining their fertility, were enrolled into a pilot study of fertility-sparing management. Diagnosis of LG-ESS was made on specimens from hysteroscopic resection performed on a presumed benign lesion. All patients were planned to be treated with adjuvant megestrol acetate for two years. Hormonal therapy was started within 6 weeks from the hysteroscopic resection, with orally megestrol acetate at 40 mg daily, increasing gradually according to patient's tolerance to the recommended total dose of 160 mg daily. Results: All patients were submitted to hysteroscopic resection in a one-step procedure. Five patients started megestrol acetate within 6 weeks from the hysteroscopic resection (one patient did not start hormonal therapy because of early pregnancy after the hysteroscopic resection). Hormonal therapy was well tolerated; one patient stopped megestrol acetate after 12 months because of self-supporting strong desire to conceive; the other four patients regularly completed the hormonal therapy. To date, all patients show no evidence of disease. Conclusions: Although fertility-sparing management is not the current standard of care for young women with early-stage LG-ESS, our preliminary data are promising. Larger series with a longer follow-up are needed to further assess safety and efficacy of combined hysteroscopic resection and hormonal therapy.